Implementation of Hand Gesture Recognition as Smart Home Devices Controller - Dewangga, Stanley; Subianto, Mochamad; Swastika, Windra (Intelligent System and Computation, 2024)
Some current virtual assistant products such as Alexa, Siri and Google Home facilitate features to control smart home devices through voice input, which has become increasingly popular in recent years. In addition to voice input, smart home devices can also be monitored and controlled through smartphones or computers using applications that provide users with flexibility. However, both control systems are less efficient, as they consume time and voice input utilization may sometimes not be recognized in crowded conditions. Therefore, this research introduces an application to recognize real-time hand gestures and utilize them for a new control system that provides time and energy efficiency. This application processes images using the Mediapipe framework, generating hand landmark outputs. These landmark outputs are utilized to determine the combination of raised or lowered fingers, which is then used to control smart home devices. The application is developed with ESP32 and ESP01s modules as data receivers from gesture recognition, and ESP32-CAM for image acquisition. Meanwhile, the gesture recognition computation process is executed on a Raspberry Pi 3 Model B. The gesture recognition application achieves good accuracy at 88%, but may experience occasional failures for certain gestures. However, the response time generated by the smart home control system is still relatively long, averaging 7.88 seconds.